The Black Cat as an Ornamental Motif in Hand-Drawn Batik for Upiak's Bedroom Aesthetic Design - Elinda, Yosi; Jupriani, Jupriani (Institut Seni Indonesia Padang Panjang, 2025)
This article explores the creation process of hand-drawn batik artworks featuring the black cat as the main motif in aesthetic bedroom furnishings for a Minangkabau girl, traditionally referred to as “Si Upiak.” The choice of the black cat was driven by the intention to challenge negative stereotypes rooted in traditional myths. Through stylized forms and the hand-drawn batik technique, the author produced seven textile works functioning as both decorative and educational elements, including bed sheets, pillowcases, night lamps, and sleepwear. Each piece combines the visual elements of the black cat and lily flowers as symbols of strength, sincerity, and comfort within a personal space. The creation process follows the stages of preparation, elaboration, synthesis, conceptual realization, and finishing. The resulting works demonstrate a blend of aesthetic, symbolic, and functional values within the context of local culture and contemporary artistic expression. This work aims to enrich the discourse of textile craft art while serving as a medium for value transformation in society.